The Concept Of Munakahat Fiqh; Role Of Husband And Wife In Forming A Samara Family (Sakinah, Mawadah, Waromah) Version Of Dhau Al-Mishbah Fi Bayani Ahkam An-Nikah By KH. Hasyim Asy'ari - Abdul Jafar, Wahyu; Fahimah, Iim (CV. Inara, 2022)
This research aims to discuss the role of husband and wife in forming a samara family in dhau al-mishbah fi Bayani ahkam an-nikah by KH. Hasyim Asy'ari. This research is a research library, while the approach used in this study is Content Analysis. The data collection technique used is the documentation technique. After conducting in-depth research, it was concluded that to make a samara family needed an excellent synergy between husband and wife. Obligation to form a samara family cannot only be imposed on the husband or wife alone, but both parties have their respective roles that must be carried out proportionally and professionally. The part that the husband must carry out is that the husband must reasonably associate with his wife, fulfil his wife's rights well, live physically and mentally, be patient with his wife's bad behaviour, provide education for his wife, especially education about sharia. 'at religion of Islam. The role that wife must carry out is to obey the husband's orders (as long as the order does not violate Shari'ah), the wife must always try to please her husband, look as beautiful as possible by maximizing her potential, must be trustworthy and not betray when her husband is not at home.